1973
DOI: 10.1002/hlca.19730560722
|View full text |Cite
|
Sign up to set email alerts
|

Proxiphomin und Protophomin, zwei neue Cytochalasane

Abstract: Herrn Prof. Edgar Ledeyer zum 65. Geburtstag gewidmet (2.5. VI. 73) Szcmmary. Two ncw cytochalasans, proxiphomin and protophomin have been isolated from culturcs of a Phoma species (strain S 298). Thcy are shown t o possess the same skeleton as deoxaphomin (4), which has been isolated recently. Thus they represent lower states of oxidation of 4. On thc basis of the spectral data, the structures 16-methyl-l0-phenyl-[13]cytochalasa-6 (7), 13t, Zlt-triene-l,23-dionc (1) 13t, 19t-trien-l,l7-dion) [5] bewiese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
2
11
0
1
Order By: Relevance
“…The formula was used for a query in Antibase2012 [34] with one resulting hit, proxiphomin ( 3 ). NMR data and optical rotation of 3 matched published data [32].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The formula was used for a query in Antibase2012 [34] with one resulting hit, proxiphomin ( 3 ). NMR data and optical rotation of 3 matched published data [32].…”
Section: Resultssupporting
confidence: 76%
“…Here we report the target-guided isolation and structure elucidation based on UV, MS, and NMR data of the two novel cytochalasins sclerotionigrin A ( 1 ) and B ( 2 ). Compounds 1 and 2 were isolated from Aspergillus sclerotioniger (IBT 22905) together with the known cytochalasin proxiphomin ( 3 ) [32]. We have previously reported ochratoxin A, ochratoxin B and pyranonigrin A from this isolate [33].…”
Section: Introductionmentioning
confidence: 99%
“…2b The structure of 4 suggested that the CcsA reductase (R) domain reductively liberated the putative thioester intermediate appended to the CcsA thiolation (T) domain to give 1. Isolation of proxiphomin 17 and procheatoglobosin I 6 (Fig. 1), non oxidatively modified putative precursors in the corresponding cytochalasan producing fungi, provides the circumstantial evidence that the first free linear intermediate has an enone moiety.…”
Section: Resultsmentioning
confidence: 93%
“…[4][5][6] It also provided a template for their total chemical syntheses. 4,7,8 His prediction of biological Baeyer Villiger reactions 9 to convert initially formed macrocyclic ketones to macrolide lactones and carbonates has also been recently conrmed using an isolated enzyme. 10 A subsequent postdoctoral year with Professor Heinz Floss at Purdue University not only provided further insights into biosynthesis, but also afforded valuable experience working with puried enzymes 11,12 (Fig.…”
Section: Introductionmentioning
confidence: 99%